Analysis of IgG with specificity for variant surface antigens expressed by placental Plasmodium falciparum isolates - Kremsner Peter G; Fievet Nadine; Staalsoe Trine; Reinhardt Christina; Khattab Ayman; Deloron Philippe; Hviid Lars; Klinkert Mo-Quen (Malaria Journal, 2004)
Abstract Background Pregnancy-associated malaria (PAM) is caused by Plasmodium falciparum- infected erythrocytes that can sequester in placental intervillous space by expressing particular variant surface antigens (VSA) that can mediate adhesion to chondroitin sulfate A (CSA) in vitro. IgG antibodies with specificity for the VSA expressed by these parasites (VSA PAM ) are associated with protection from maternal anaemia, prematurity and low birth weight, which is the greatest risk factor for death in the first month of life. Methods In this study, the development of anti-VSA PAM antibodies in a group of 151 women who presented to the maternity ward of Albert Schweitzer Hospital in Lambaréné, Gabon for delivery was analysed using flow cytometry assays. Plasma samples from placenta infected primiparous women were also investigated for their capacity to inhibit parasite binding to CSA in vitro. Results In the study cohort, primiparous as well as secundiparous women had the greatest risk of infection at delivery as well as during pregnancy. Primiparous women with infected placentas at delivery showed higher levels of VSA PAM -specific IgG compared to women who had no malaria infections at delivery. Placental isolates of Gabonese and Senegalese origin tested on plasma samples from Gabon showed parity dependency and gender specificity patterns. There was a significant correlation of plasma reactivity as measured by flow cytometry between different placental isolates. In the plasma of infected primiparous women, VSA PAM -specific IgG measured by flow cytometry could be correlated with anti-adhesion antibodies measured by the inhibition of CSA binding. Conclusion Recognition of placental parasites shows a parity- and sex- dependent pattern, like that previously observed in laboratory strains selected to bind to CSA. Placental infections at delivery in primiparous women appear to be sufficient to induce functional antibodies which can both recognize the surface of the infected erythrocytes as well as block their binding ...